Green signals: Energy efficiency and German housing markets - Francisco Amaral; Morgane Soufflet; Jonas Zdrzalek; Steffen Zetzmann (Kiel Institute for the World Economy (IfW Kiel), 2024)
In this study, we analyze the effect of energy performance certificates on sales prices and rents on the basis of millions of sales and rental listings in Germany in order to understand the causes of the stagnation of the refurbishment rate in the German housing stock. The results show that higher energy efficiency is reflected in higher prices and rents. Sales and rent premiums for energy-efficient buildings are higher when using the so-called Bedarfsausweis (energy demand certificate), which is based on an expert evaluation of the property's energy status. However, these premiums are noticeably lower when using the so-called Verbrauchsausweis (energy consumption certificate), which relies on the meter readings from the past three years. The rent premium for energy efficient dwellings can be fully explained by the energy cost savings when switching from low to high energy efficiency using the Bedarfsausweis. This suggests that when accurate information is available, market participants correctly internalize energy cost savings. Comparing the sale price premium with refurbishment costs suggests that refurbishment is financially viable, but only if the Bedarfsausweis is used. Despite mandatory energy performance certificates, a significant portion of property listings do not provide this information, suggesting the need for stricter enforcement. Policy recommendations: Strengthen the quality of energy performance certificates by focusing on the Bedarfsausweis and phasing out the Verbrauchsausweis. In addition, strengthen compliance with reporting requirements for energy performance certificates by introducing a sanction mechanism. This will increase transparency and can therefore contribute to an increase in the refurbishment rate. – – In dieser Studie analysieren wir auf Grundlage von Millionen Verkaufs- und Mietinseraten in Deutschland den Effekt von Energieausweisen auf Verkaufspreise und Mieten, um die Ursachen für die Stagnation der Sanierungsrate im Wohnungsbestand zu verstehen. Die Ergebnisse zeigen, dass höhere Energieeffizienz in höheren Preisen und Mieten widergespiegelt wird. Verkaufs- und Mietprämien für energieeffiziente Gebäude sind höher, wenn der Bedarfsausweis verwendet wird, der auf einer Expertenbewertung des energetischen Zustands der Immobilie basiert. Die Prämien sind jedoch deutlich niedriger, wenn der Verbrauchsausweis verwendet wird, der sich auf die Energieverbrauchsdaten der letzten drei Jahre stützt. Die Mietprämie für energieeffiziente Wohnungen kann vollständig durch die Energiekosteneinsparungen beim Wechsel von niedriger zu hoher Energieeffizienz erklärt werden, wenn ein Bedarfsausweis verwendet wird. Dies deutet darauf hin, dass Marktteilnehmer Energiekosteneinsparungen korrekt einpreisen, wenn genaue Informationen verfügbar sind. Der Vergleich von Verkaufspreisen mit energetischen Sanierungskosten legt nahe, dass eine Sanierung finanziell rentabel ist, aber nur, wenn der Bedarfsausweis verwendet wird. Trotz der Pflicht zu Energieausweisen enthält ein erheblicher Teil der Immobilienanzeigen diese Informationen nicht, was auf die Notwendigkeit strengerer Durchsetzung hindeutet. Politikempfehlungen: Verbesserung der Qualität der Energieausweise durch die Etablierung des Bedarfsausweises als Standard und die schrittweise Abschaffung des Verbrauchsausweises. Darüber hinaus sollte die Einhaltung der Meldepflichten für Energieausweise durch die Einführung eines Sanktionsmechanismus gestärkt werden. Dies wird zu mehr Transparenz führen und kann somit zu einer Steigerung der Sanierungsrate beitragen.
Keywords: 330; Energy efficiency; German Housing Markets; Energy Performance Certificates; Refurbishment; Energieeffizienz; Deutsche Wohnungsmärkte; Energieausweise; Sanierung